2006
DOI: 10.3133/sir20065112
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Frequency of Floods in New York

Abstract: This report includes a Geographic Information System (GIS) tool to compute basin characteristics used in the regional regression equations included with the report. It is the responsibility of the user to use the tool properly and to verify that the results are meaningful. The user is cautioned that although the tool has been tested, future uses might reveal errors that were not detected during testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…For the 10‐year event, regulated flow in the Upper Hudson is now about 300 m 3 /s less than prior to dam construction, and for the 100‐year event the reduction is about 800 m 3 /s. The calculated recurrence intervals were similar to previously published analyses of the predam discharge record (Lumia et al, ; Figure ). Using the relationship between discharge and water level observed prior to 1930 of 1.6 m per 1,000 m 3 /s (Figure ), the decrease in flow for the 10‐year event corresponded to a decrease in water level of 0.5 m, and the 100‐year flow event water level decreased by 1.3 m. The total decreases in water level for the 10 and 100‐year water levels at Albany (2.6 and 2.0 m, Figure ) were greater than these decreases due to flow regime alone, indicating that the net reduction in flood risk is due both to flow regulation and channel deepening in the estuary.…”
Section: Results and Interpretationsupporting
confidence: 87%
See 1 more Smart Citation
“…For the 10‐year event, regulated flow in the Upper Hudson is now about 300 m 3 /s less than prior to dam construction, and for the 100‐year event the reduction is about 800 m 3 /s. The calculated recurrence intervals were similar to previously published analyses of the predam discharge record (Lumia et al, ; Figure ). Using the relationship between discharge and water level observed prior to 1930 of 1.6 m per 1,000 m 3 /s (Figure ), the decrease in flow for the 10‐year event corresponded to a decrease in water level of 0.5 m, and the 100‐year flow event water level decreased by 1.3 m. The total decreases in water level for the 10 and 100‐year water levels at Albany (2.6 and 2.0 m, Figure ) were greater than these decreases due to flow regime alone, indicating that the net reduction in flood risk is due both to flow regulation and channel deepening in the estuary.…”
Section: Results and Interpretationsupporting
confidence: 87%
“…The diamond markers are unbiased return intervals based on rank‐ordered data (e.g., Makkonen, ). Return intervals calculated by the USGS for the same data prior to discharge regulation but using log‐Pearson type III and regional regression analyses (Lumia et al, ) are shown for reference.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…The peak flows (discharge) during the floods of August and September 2011 were estimated for each ungaged study site by scaling USGS reference stations reported peak discharge magnitude or the AEP of that discharge, using a USGS watershed characteristics database called StreamStats. StreamStats was used to delineate the ungaged drainage–basin boundary and estimate the peak flows associated with standard flood AEP (Ries, Guthrie, Rea, Steeves, & Stewart, ) using regional regression equations devised between basin characteristics and long‐term USGS discharge records, by hydro‐physiographic region (Lumia, Freehafer, & Smith, ). The flood discharge and AEP associated with the Irene and Lee storms at each ungaged site were estimated using two methods, and the most extreme values (i.e., largest discharge, smallest AEP) were used to assess relationships with changes in macroinvertebrate metrics following the floods.…”
Section: Methodsmentioning
confidence: 99%
“…The flood discharge and AEP associated with the Irene and Lee storms at each ungaged site were estimated using two methods, and the most extreme values (i.e., largest discharge, smallest AEP) were used to assess relationships with changes in macroinvertebrate metrics following the floods. The first method estimated ungaged peak discharge, Q u‐P , as the product of the ratio of watershed areas, A u /A g and the observed peak discharge, Q g‐P , where A u is the ungaged watershed area and A g is the gaged watershed area (Lumia et al, ). Then the Q u‐P was used in StreamStats to interpolate between the regional regression flood discharge values and identify the associated AEP u‐P for the ungaged peak flood.…”
Section: Methodsmentioning
confidence: 99%
“…LP3 is the recommended distribution in the United States (typically for flood analysis), Australia, Taiwan, Pakistan, and Nigeria [52][53][54][55][56][57].…”
Section: Log-pearsonmentioning
confidence: 99%